Rhythm Facilitates the Detection of Repeating Sound Patterns - Rajendran, Vani G.; Harper, Nicol S.; Abdel-Latif, Khaled H. A.; Schnupp, Jan W. H. (Frontiers in Neuroscience, 2016)
This study investigates the influence of temporal regularity on human listeners’ ability to detect a repeating noise pattern embedded in statistically identical non-repeating noise. Human listeners were presented with white noise stimuli that either contained a frozen segment of noise that repeated in a temporally regular or irregular manner, or did not contain any repetition at all. Subjects were instructed to respond as soon as they detected any repetition in the stimulus. Pattern detection performance was best when repeated targets occurred in a temporally regular manner, suggesting that temporal regularity plays a facilitative role in pattern detection. A modulation filterbank model could account for these results.